FAKTOR-FAKTOR YANG MEMPENGARUHI IMPLEMENTASI KEBIJAKAN PENGENDALIAN TUBERKULOSIS DI LEMBAGA PEMASYARAKATAN KELAS I CIPINANG - Rahmayanti, Dyah; Salomo, Roy V (Jurnal PubBis, 2020)
Even though the implementation of TB control policies has been implemented in prisons, the number of prisoners suffering from it still high as it happened in Cipinang Prison Class I. The purpose of this study is to analyze the factors that influence the implementation of TB control policies in Cipinang Prison Class I based on the theory of policy implementation from Mazmanian and Sabatier (1989). This theory identifies various variables that affect the achievement of objectives in the overall implementation process. The data in this study were collected through the literature review method while still paying attention to the credibility of the data source. The results showed that apart from the intrinsic factors of the prison itself, leadership commitment, clarity of policy content, and collaboration between sectors are the factors that influence the implementation of TB control policies. Therefore, in the future it is necessary to conduct a deeper study which elaborate more of these factors. Hopefully by analyzing more of these factors will develop comprehensive strategies to achieve the policy. Keywords: Policy implementation, tuberculosis, prison